The Relationship of Professional Competence with Teacher Work Productivity in Madrasah Aliyah - Ayu Asmarani; Sukarno Sukarno; Minnah El Widdah (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this study was to determine whether there was a relationship between professional competence and teacher work productivity at Madrasah Aliyah Negeri 1 Batang Hari. This type of research approach is quantitative. The research population of teachers at Madrasah Aliyah Negeri 1 Batang hari was 30 people, using a saturated sampling technique (census). The data collection technique used a questionnaire (questionnaire), and the data were analyzed using simple correlation analysis. The results showed that there was a positive and significant relationship between professional competence and teacher work productivity, with the obtained t count value > t table value (7,75415> 1,7011) and p value 0,000. Then obtained an r value of 0,826, which states that there is a strong relationship between professional competence and teacher work productivity. The amount of the effective contribution of the professional competency variable with the teacher work productivity variable was 70,2%. Thus, the better the professional competence of teachers, the more teacher work productivity will increase.